The adverse impact of obesity on heart rate variability is modified by a NFE2L2 gene variant: The SAPALDIA cohort. (1st February 2017) - Adam, Martin; Imboden, Medea; Schaffner, Emmanuel; Boes, Eva; Kronenberg, Florian; Pons, Marco; Bettschart, Robert; Barthelemy, Jean-Claude; Schindler, Christian; Probst-Hensch, Nicole
Abstract: Background: Overweight has been associated with an increase in inflammatory markers and with an imbalance in the autonomic nervous system, such as a decrease in heart rate variability (HRV). In this study we aimed to investigate the modifying effect of a genetic variation in a major anti-inflammatory marker gene, NFE2L2, on the relationship between overweight and HRV. Methods: We analyzed participants of the SAPALDIA cohort aged 50 years and older, twice in 2002/2003 (N = 1472) and 2010/2011 (N = 1235). We included persons with valid genotype data, who underwent ambulatory 24-h electrocardiogram monitoring, and reported on medical history and lifestyle. The association between HRV and BMI, measured as standard deviation of normal-to-normal intervals (SDNN) by BMI and the modifying effect of the cardiovascular health-related NFE2L2 gene variant rs2364723 were tested, applying multivariable mixed linear regression models. Results: We found study participants with overweight (BMI > 25) over two follow-up surveys 10 years apart to have a negative association between SDNN, calculated as geometric means, with BMI. The examined NFE2L2 variant sustainably modified (pinteraction = 0.014) the found inverse association between a BMI increment and SDNN, causing a stronger decrement in SDNN for participants with the CC genotype (− 20.7%; 95%-confidence interval: − 12.33 to − 28.28) compared with participants carrying the GC (− 7.43; 95%CI: − 3.56 to − 11.15) or GG (− 11.26%; 95%CI: − 7.68 to − 14.7) genotype, estimated for the difference from the 90 th to the 10 th percentile of BMI by the NFE2L2 variant. Conclusions: Our results are consistent with the hypothesis that overweight decreases heart rate variability through inflammatory processes.